Examining Accreditation Readiness of PTKIN Master’s Programs in Arabic Language Education - Zainal Muttaqin; Raswan Raswan; Shifany Maulida Hijjah; Savinatul Jannah; Keysa Tamami (Institut Agama Islam Negeri Curup, 2026)
Program accreditation is a primary standard for assessing the quality and credibility of higher education. The Master’s Program in Arabic Language Education (MPBA) at PTKIN demonstrates its commitment to academic excellence through rigorous accreditation preparations, encompassing curricula, human resources, infrastructure, and research performance. However, a significant research gap exists, as limited comparative research explores how internal and external factors influence accreditation outcomes across similar programs; most existing studies remain descriptive and context-specific rather than generalizable. This study analyzes the readiness of the MPBA Program at PTKIN for national accreditation by LAMDIK. The evaluation was conducted based on accreditation standards ranging from vision and governance to program outcomes and impact. Using a qualitative-descriptive method—incorporating interviews, document analysis, and observation—this study finds that the MPBA has met most standards, particularly in its globally oriented curriculum, international partnerships, and human resource development. Nevertheless, challenges persist in strengthening governance, increasing international publications, and enhancing learning facilities. These results offer strategic recommendations for program managers to improve accreditation readiness through synergy, data-driven planning, and continuous innovation, while serving as a benchmark for other programs navigating accreditation in the era of educational globalization.